2015
DOI: 10.1007/s11589-015-0136-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of postseismic deformation parameters from continuous GPS data in northern Sumatra after the 2004 Sumatra-Andaman earthquake

Abstract: Continuous global positioning system (GPS) in northern Sumatra detected signal of the ongoing physical process of postseismic deformation after the M9.2 2004 Sumatra-Andaman earthquake. We analyze the characteristics of postseismic deformation of the 2004 earthquake based on GPS networks operated by BIG, and the others named AGNeSS, and SuGAr networks located in northern Sumatra. We use a simple analytical logarithmic and exponential function to evaluate the postseismic deformation parameters of the 2004 earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…As shown in Tables 2 and 3, there were only small differences between RMS results, as a result of the sensitivity of the availability of early GPS data just after earthquake occurrences to the logarithmic and exponential functions. As reported for other earthquake cases, such as the 2004 M9.2 SumatraAndaman earthquake (Anugrah et al 2015), the 2005 M8.7 Nias earthquake (Kreemer et al 2006), the 2007 M8.5 Bengkulu earthquake (Alif et al 2016), and the 2010 M7.8 Mentawai earthquake (Ardika et al 2015), they obtained a better data fit using logarithmic function for the early postseismic GPS data.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…As shown in Tables 2 and 3, there were only small differences between RMS results, as a result of the sensitivity of the availability of early GPS data just after earthquake occurrences to the logarithmic and exponential functions. As reported for other earthquake cases, such as the 2004 M9.2 SumatraAndaman earthquake (Anugrah et al 2015), the 2005 M8.7 Nias earthquake (Kreemer et al 2006), the 2007 M8.5 Bengkulu earthquake (Alif et al 2016), and the 2010 M7.8 Mentawai earthquake (Ardika et al 2015), they obtained a better data fit using logarithmic function for the early postseismic GPS data.…”
Section: Discussionsupporting
confidence: 62%
“…This is much longer than that for a general megathrust earthquake (Bürgmann et al 2001;Freed 2007;Anugrah et al 2015). Those analyses showed that for an M6-8 class earthquake, 2005 M8.7 Nias Earthquake (Kreemer et al, 2006) 2010 M7.8 Mentawai Earthquake (Ardika et al, 2015) 2004 M9.2 Sumatra−Andaman Earthquake (Anugrah et al, 2015) 2004 M6.0 Parkfield Earthquake (Freed, 2007) 1997 M7.8 Kronotsky Earthquake (Burgmann et al, 2001) 2006 M7.8 Java Tsunami Earthquake Fig. 5 Correlation between decay time after earthquake occurrences and earthquake magnitude for various earthquake cases the decay time value is *10 days.…”
Section: Discussionmentioning
confidence: 88%
“…It could capture coseismic displacements [5,8], postseismic displacements [2,20], and also interseismic displacements [9,16,17]. Continu ous GPS time series data after an earthquake occurrence could also be used to determine the most appropriate and comprehensive model of coseismic slip distribution [6].…”
Section: Research Articlementioning
confidence: 99%
“…The recent strong earthquakes present examples where the macroscopic post-seismic deformation is interpreted in view of the above relaxation mechanisms, which are based on the assumption of a single relaxation time estimated for each post seismic relaxation observed [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%